2006
DOI: 10.4269/ajtmh.2006.74.54
|View full text |Cite
|
Sign up to set email alerts
|

Pupal Habitat Productivity of Anopheles Gambiae Complex Mosquitoes in a Rural Village in Western Kenya

Abstract: The productivity of larval habitats of the malaria vector Anopheles gambiae for pupae (the stage preceding adult metamorphosis) is poorly known, yet adult emergence from habitats is the primary determinant of vector density. To assess it, we used absolute sampling methods in four studies involving daily sampling for 25 days in 6 habitat types in a village in western Kenya. Anopheles gambiae s.s. comprised 82.5% of emergent adults and Anopheles arabiensis the remainder. Pupal production occurred from a subset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
123
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(138 citation statements)
references
References 21 publications
13
123
1
1
Order By: Relevance
“…At our Kenya Medical Research Institute (KEMRI) study site in Kisian, Kenya (near Kisumu), depths of puddles serving as larval An. gambiae habitats vary 3±3 (S.E.M) cm each day (Mutuku et al 2006). Thunderstorms frequently deliver rain to a region, but they irregularly form or renew puddles at a given site.…”
Section: Introductionmentioning
confidence: 99%
“…At our Kenya Medical Research Institute (KEMRI) study site in Kisian, Kenya (near Kisumu), depths of puddles serving as larval An. gambiae habitats vary 3±3 (S.E.M) cm each day (Mutuku et al 2006). Thunderstorms frequently deliver rain to a region, but they irregularly form or renew puddles at a given site.…”
Section: Introductionmentioning
confidence: 99%
“…By definition, egg deposition by Anopheles gambiae sensu lato determines the distribution of larvae of this important malaria vector in nature, which in turn influences resultant production of the adults (Mutuku et al 2006b). An.…”
mentioning
confidence: 98%
“…Secondly, such pools are temporary and therefore contain fewer or no competitors and predators decreasing the larvae mortality rate (Koenraadt et al, 2004;Sunahara et al, 2002). Thirdly, human activities contribute to the creation of these habitats which are found near human settlements and thus time spent by the gravid mosquito to locate surface water for oviposition is reduced (Mutuku et al, 2006b;Minakawa et al, 1999). Another critical factor determining mosquito breeding habitat productivity is its stability because only habitats that persist long enough can produce adult mosquitoes (Gianotti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mosquitoes may exploit any available water for oviposition, natural or man-made (Imbahale et al, 2011;Fillinger et al, 2004), permanent or temporary (Fillinger et al, 2004), clean or polluted (Sattler et al, 2005;Awolola et al, 2007;Chinery, 1984) and of various sizes from hoof-prints of animals to the edges of large water bodies (Sattler et al, 2005;Mutuku et al, 2006b;Imbahale et al, 2011), although individual species have preferences of habitat type. For example, Anopheles gambiae complex mosquitoes, the principal malaria vector in Sub-Sahara Africa prefer temporary, sunlit water bodies for their breeding, which become abundant during the rainy season (Mutuku et al, 2006a;Minakawa et al, 2004), although their larvae have also been found in polluted waters (Imbahale et al, 2011;Awolola et al, 2007;Sattler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%